Pendekatan Hidrogeomorfologi Dan Pendugaan Geolistrik Untuk Identifikasi Potensi Airtanah Di Jedong Malang - Ferryati Masitoh; Alfi Nur Rusydi; Ilham Diki Pratama (Universitas Negeri Gorontalo, 2021)
This study aims to identify the potential groundwater in Jedong, Malang, East Java. The hydrogeomorphological approach is a suitable approach to describe the relationship between hydrological and geomorphological processes on and below the earth's surface. The survey of geoelectricity complements the hydrogeomorphological approach. It will give a better description of the groundwater conditions below the earth's surface. Based on the research, there are 2 hydrogeomorphological units in the study area, which are: Volcanic Foot Valley Unit and Volcanic Foot Ridge Unit. The best groundwater potential is in Volcanic Foot Valley Hydrogeomorphological unit, namely Awar-awar Valley and Cokro Valley. The valleys are dominated by gully erosion and landslides. They have surface deposits up to a depth of 7 meters, and lots of outcrops of breccia, pumice, and andesite boulders. The valley’s springs discharge between 56 - 198 m3/day. The average infiltration rate in the valley is 1776 mm / hour, with sandy soil material. The best aquifer consisting of sandy material is more than 10 meters in depth, based on the geoelectrical survey. Water in the aquiclude layer, cannot be exploited because it is breccia and tuff material. The Sawah valley cannot be exploited further because the groundwater potential is very low. This can be identified by the thick water outflow seepage. In the Volcanic Foot Ridge Hydrogeomorphological unit, the groundwater potential is also very small. Hydrogeomorphically, water will flow down the slope to the valley. It will reduce the infiltration rate. In general, the ridge area is only used for settlement, while the slopes are used for dryland agriculture. The geoelectric analysis results show that the groundwater potential is at a depth of more than 45 meters. This research’s results show that the combination of the hydrogeomorphological approach and the geoelectric use will provide a better description of the potential groundwater.